(untitled) (American Journal of Islam and Society, 2014)
Although not as comprehensive as the articles featured in this special issue, this editorial presents my comments and the results of my survey conducted among professors and lecturers who teach Islamic studies in Ghanaian universities. For a comparative perspective, similar questions were also sent to colleagues in Nigeria. I undertook this preliminary research to prepare myself for a roundtable discussion that was held at the annual African Studies Association meeting (Philadelphia, November 29-December 1, 2012) on “The Study of Islam in African Universities: Is it a Priority?” Based on my own on-the-ground knowledge and what I gathered from my survey’s respondents, this topic does not seem to be a priority for Ghana’s university administrators (viz., the presidents, vice chancellors, and deans all the way down to the department heads and their administrative support), students, parents, or policymakers. In general terms, Ghana’s university administrators see no value in supporting this stream of study because it does not “produce” graduates who can make constructive contributions to the national agenda of industrial development. The study of religion (or religious studies) in general suffers from this bias internationally, and religion itself is becoming less popular among young people. Other indications of this low priority are the courses offered in religious studies departments and the lack of “suitable” experts. After my presentation, one audience member who had earned a PhD in Islamic studies from a Middle Eastern university, pointed out that he could not find a teaching job in a Ghanaian university. He seemed to believe that his situation had a lot to do with discrimination and bias; however, I was not so sure. He is now an adjunct instructor in Islamic studies at a local junior college in the Philadelphia area. Of Ghana’s 8 public and 48 private universities,1 only 5 or six 6 have departments that include Islam in their courses listings.2 Apart from the newly established Islamic University College, which is not included here because it is an Islamic university, none of the leading universities offer a major or a minor in Islamic studies. The University of Ghana (Accra) does come close, ...